Komputasi dinamika fluida pada T–mikro mixer - Putri Ramadhany (Jurnal Rekayasa Proses, 2017)
Fluid diffusion can occur effectively if a high gradient concentration exists in every part of the fluid. This can be achieved by decreasing the cross section area of the channel into micro size. The miniatur size of micro mixer can be very effective for molecular diffusion in the mixing process. In this research, the modeling of mixing and heat transfer in the passive micro mixer was conducted. T-shaped mixer was chosen as micro mixer. Water was used as medium and passive tracers were added to differentiate water profile from two different inlets. Mixing and heat transfer profiles inside the T-micro mixer were observed. The computational fluid dynamics (CFD) modeling of mixing and heat transfer in the T-micro mixer was completed by ANSYS®. The effect of geometry and average input velocity of fluids on mixing process were observed. The result of this research included: (1) When the laminar flow is the dominant flow (Re is 25), the tracer mixing is not particularly seen. The tracer mixing is observed when the average velocity is increased (Re increases), (2) The heat flux to the wall (4.85x10-6 Watt/m2) occurred when T–micro mixer is no longer isothermal, (3) The scale–up to factor ten does not necessarily improve the mixing performance (Re is kept constant), and (4) When the shape of cross section is changed to circle (cross section area is kept constant), the mixing performance is not necessarily improved.